Plant Pathology - Joseph Cumagun, Christian R. (IntechOpen, 2012)
Plant pathology is an applied science that deals with the nature, causes and control of plant diseases in agriculture and forestry. The vital role of plant pathology in attaining food security and food safety for the world cannot be overemphasized.